EEG‐fMRI in atypical benign partial epilepsy. Issue 8 (12th June 2013) - Moeller, Friederike; Moehring, Jan; Ick, Imke; Steinmann, Elisabeth; Wolff, Stephan; Jansen, Olav; Boor, Rainer; Stephani, Ulrich; Siniatchkin, Michael
Summary Atypical benign partial epilepsy (ABPE) is a subgroup among the idiopathic focal epilepsies of childhood. Aim of this study was to investigate neuronal networks underlying ABPE and compare the results with previous electroencephalography (EEG)–functional magnetic resonance imaging (fMRI) studies of related epilepsy syndromes. Ten patients with ABPE underwent simultaneous EEG‐fMRI recording. In all 10 patients several types of interictal epileptiform discharges (IEDs) were recorded. Individual IED‐associated blood oxygen level–dependent (BOLD) signal changes were analyzed in a single subject analysis for each IED type (33 studies). A group analysis was also performed to determine common BOLD signal changes across the patients. IED‐associated BOLD signal changes were found in 31 studies. Focal BOLD signal changes concordant with the spike field (21 studies) and distant cortical and subcortical BOLD signal changes (31 studies) were detected. The group analysis revealed a thalamic activation. This study demonstrated that ABPE is characterized by patterns similar to studies in rolandic epilepsy (focal BOLD signal changes in the spike field) as well as patterns observed in continuous spikes and waves during slow sleep (CSWS) (distant BOLD signal changes in cortical and subcortical structures), thereby underscoring that idiopathic focal epilepsies of childhood form a spectrum of overlapping syndromes.